Beyond Postcapitalist Economy: Toward a Pluriversal Politics of Transformation in Massachusetts. Issue 1 (2nd January 2023) - Loh, Penn
Abstract : In the last decade, a solidarity-economy movement has emerged in Massachusetts, with desires to fight against the world as it is and build the world as it should be. This orientation toward a postcapitalist economy helps to overcome capitalocentrism and sparks the radical imagination. But in trying to build elements of a solidarity economy, such as worker cooperatives and community land trusts, this movement has encountered contradictions stemming from the growth mindset of a modernist Western ontology that posits the existence of but one singular reality. As the movement now tries to move beyond a postcapitalist economy as the goal and toward creating other worlds and ways of being, it is valuing and intentionally cultivating more relational ways of being, centering solidarity and care in all the ways that we exist in interdependence with one another and with Earth's living systems. In the solidarity-economy movement, pluralism is an opening to building the pluriverse.